LAW AND NEUROETHICS: CHALLENGING THE PARADIGM OF JUSTICE IN THECONTEXT OF ADVANCES IN NEUROSCIENCES AND DECISION-MAKING TECHNOLOGIES - Yuarini Wahyu Pertiwi; Enden Suryati; Hapipi Jayadi; Aida Fitriani; Syamsul Ma'arif (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study delves into the intricate relationship between law and neuroethics, critically examining the evolving paradigm of justice in light of advancements in neurosciences and decision-making technologies. As neuroscientific technologies provide unprecedented insights into the human mind, integrating neuroscientific evidence into legal frameworks poses challenges and opportunities. Critiquing current approaches highlights limitations within existing legal systems and ethical considerations, necessitating careful reforms and adaptations. Ethical critiques by scholars and ethicists prompt reevaluating the intersection between law and neuroethics. Proposed reforms include strategies for integrating neuroethics into legal frameworks and legislative changes to address emerging ethical complexities. The discussion extends to critical areas for future research, emphasizing the need to identify unresolved questions and encourage interdisciplinary collaboration. The implications for the future underscore a shift towards a legal landscape that prioritizes ethical considerations in using neuroscientific evidence.